Pengembangan Aplikasi Pengolahan Data Penilaian Peserta Praktek Kerja Lapangan di Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat - Hendra Gunawan; M. Fahmi Nugraha; Diana Novita (Jurnal Accounting Information System (AIMS), 2022)
Field work practices at the Library and Archival Office of West Java Province are currently still done manually, namely by way of guidance provides value written on the value information paper submitted to the coordinator to then be entered into data processing applications such as Microsoft word and excel, Also correcting post prekerin examinations that are done manually by equating the answer with the answer kuci printed on paper, so it takes a long time and involves many parties in working on it. The method of system development used is the waterfall method. This method includes stages namely Analysis and definition, system and software design, unit implementation and testing, system integration and testing, and system operation and maintenance. The system uses XAMPP as a web server for system design and MySQL as a database. The result of this research is the Application of Data Processing Of Participants Field Work Practices that make certificates automatically stamped that can minimize miscalculation in the accumulation of value obtained, in addition to minimizing resources are also able to provide access to the presentation of information quickly.